Mass dispersion from an instantaneous line source in a turbulent shear flow - Putta, S. N., author; Cermak, J. E. (Jack E.), author; Fluid Dynamics and Diffusion Laboratory, College of Engineering Colorado State University, publisher (Colorado State University. Libraries, 1971)
Dispersion of passive material released from an instantaneous line source in the constant stress region of a neutral atmosphere is investigated. Concentration fields within the cloud of dispersing material is represented by a three dimensional density function. This density function is divided into a marginal density function and a conditional longitudinal density function. The marginal density function gives the vertical spread of the material. This function has been derived from the semiempirical equation of dispersion, by using logarithmic velocity distribution for mean velocity and a linear variation for eddy diffusivity in the vertical direction. Longitudinal density function, which gives the longitudinal distribution of material within a given horizontal layer of the cloud, is constructed from the statistical properties of dispersion. Utilizing the Lagrangian similarity hypothesis for the concentration field, the semiempirical equation has been transformed into a similarity coordinate plane. Moment equations are derived from this equation using suitable boundary conditions. From these equations statistical properties are derived for mean, variance and skewness coefficients of the longitudinal density function. It is shown that the longitudinal density function can be well represented by the Gram-Charlier density simply by substituting the derived statistical properties. Ground level concentrations obtained by integration of this proposed density function agree qualitatively with observations in wind tunnels and field experiments.
CER71-72SNP-JEC1.
June 1971.
Prepared under Office of Naval Research contract no. N00014-68-A-0493-0001 project no. NR 62-414/6-6-68 (Code 438).
Circulating copy deaccessioned 2020.
Keywords: Micrometeorology; Turbulent diffusion (Meteorology); Air -- Pollution; Atmospheric circulation